1982
DOI: 10.1111/j.1749-6632.1982.tb39488.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimanic, Antidepressant, and Antipanic Effects of Opiates: Clinical, Neuroanatomical, and Biochemical Evidence

Abstract: These clinical data may offer some support for the hypothesis that opiates have antidepressant, antimanic, and antipanic effects. This hypothesis should be studied directly by double-blind studies of the effects of exogenous and synthetic endogenous opioid peptides in patients with major depressive illness, panic and anxiety states, schizophrenia, and schizo-affective illness. These clinical data support our studies in nonhuman primates and man which suggest a common LC or NE hyperactivity may underly both dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 43 publications
0
23
1
Order By: Relevance
“…Numerous clinical observations support the involvement of the opioid system in the morbidity of depression (Verebey et al, 1978; Gold et al, 1982). Animal studies have shown that acute morphine administration increases immobility in the forced swim test (Amir, 1982; Zurita and Molina, 1999) and water wheel test (Kastin et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical observations support the involvement of the opioid system in the morbidity of depression (Verebey et al, 1978; Gold et al, 1982). Animal studies have shown that acute morphine administration increases immobility in the forced swim test (Amir, 1982; Zurita and Molina, 1999) and water wheel test (Kastin et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Methadone maintenance has been observed to achieve major mood stabilization in bipolar 1 patients; this supports the idea that opioid agonists may display an antimanic effect. 15,42,43,70,71 The fact is that, contrary to PSYc pairs, BIP1 patients who use street opioids, beyond the effect on their psychopathology, show a faster and more severe progression of their addictive disease. Even in this case, however, the fast kinetics of street opioids could explain a biphasic action on patients' concomitant psychopathology: initially favorable, and then no longer effective.…”
Section: Discussionmentioning
confidence: 92%
“…A later study found that cyclothymia, and to a lesser extent irritable traits could represent the temperamental profile of heroin addicts Maremmani et al, 2009). In the last decade the impact of opioids on psychopathology has been investigated (Comfort, 1977;Emrich et al, 1982;Gold et al, 1982;Maremmani et al, 2014b) and although results cannot rule out the possibility that bipolar heroin addicts use heroin in a self-therapeutic manner, any initial beneficial effect exerted by the substance on emotional instability would soon be followed by a mood-destabilizing action, which would accelerate the course of the illness and ultimately lead to a worse clinical presentation, both on the addictive and psychopathological plane . The link between bipolarity and substance abuse is still an open and unclear issue.…”
Section: Discussionmentioning
confidence: 99%